Problems and Solutions to alleviate Poverty in Nepal (Patan Pragya, 2021)
Poverty is one of the main problems in Nepal. In order to alleviate poverty various attempts have been implemented for poverty reduction. As per the policies of the periodic plan that started six decades ago different programmes are conducted. Both national as well as international organizations are carrying out research activities to alleviate poverty. According to the 9th plan (1997-2002), the percent of population under poverty line was 38 percent which was aimed to reduce to 30 percent as per the 10th plan (2002-2007) but remained unsuccessful. While in the 12th plan (2012-2017) the percent of population under the poverty line was successfully reduced to 25.2 percent. According to the NLSS survey report the percent of population under the poverty line in the year 1995/96, 2003/04 and 2010/11 was 41.8 percent, 30.9 percent and 25.2 percent respectively. With long term economic growth poverty, inequality and unemployment can be eliminated. But it is definitely a challenge. However, the 13th plan (2070/71-2072/73) and 14th plan (2073/74-2075/76) reduced the poverty percent to 21.6 percent and 18.7 percent respectively. Similarly, in the 15th plan (2076/77-2080/81) targeted to reduce the poverty from 18.7 percent to 11.0 percent. Finally, poverty is assumed to be zero by the year 2100/01 (NPC 15th Plan2076/77-2080/81). But this is a big challenge due to the Covid-19 pandemic and its second wave, because Nepalese living below the poverty line are highly vulnerable due to Covid pandemic.